Stability Indicating HPLC Determination of Risperidone in Bulk Drug and Pharmaceutical Formulations - Zarna R. Dedania; Ronak R. Dedania; Navin R. Sheth; Jigar B. Patel; Bhavna Patel (International Journal of Analytical Chemistry)
The objective of the current study was to develop a validated stability-indicating assay method (SIAM) for risperidone after subjecting it to forced decomposition under hydrolysis, oxidation, photolysis, and thermal stress conditions. The liquid chromatographic separation was achieved isocratically on a symmetry C18 column (5 μm size, 250 mm × 4.6 mm i.d.) using a mobile phase containing methanol: acetonitrile (80 : 20, v/v) at a flow rate of 1 mL/min and UV detection at 280 nm. Retention time of risperidone was found to be 3.35±0.01. The method was linear over the concentration range of 10–60 μg/mL(𝑟2=0.998) with a limit of detection and quantitation of 1.79 and 5.44 μg/mL, respectively. The method has the requisite accuracy, specificity, sensitivity, and precision to assay risperidone in bulk form and pharmaceutical dosage forms. Degradation products resulting from the stress studies did not interfere with the detection of Risperidone, and the assay is thus stability indicating.